If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(z + -4) + 4z + -4 = 0 Reorder the terms: 4(-4 + z) + 4z + -4 = 0 (-4 * 4 + z * 4) + 4z + -4 = 0 (-16 + 4z) + 4z + -4 = 0 Reorder the terms: -16 + -4 + 4z + 4z = 0 Combine like terms: -16 + -4 = -20 -20 + 4z + 4z = 0 Combine like terms: 4z + 4z = 8z -20 + 8z = 0 Solving -20 + 8z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 8z = 0 + 20 Combine like terms: -20 + 20 = 0 0 + 8z = 0 + 20 8z = 0 + 20 Combine like terms: 0 + 20 = 20 8z = 20 Divide each side by '8'. z = 2.5 Simplifying z = 2.5
| 7x-4+36=4x+47 | | 2(n+1)=5n-7 | | 0.2(b+3)+0.8b=-4.4 | | -27+15-22z=31 | | -1=-3r | | -4y+4=15 | | 3(5z-3)-2(z-9)= | | -4y+4=10 | | Uk+uz=x | | 29=b/-4+5 | | -65=24 | | 2(n+3)=5n-7 | | -7n+9+13n=3n-6+7n | | 2(4y-6)-24= | | 4x=18-9y | | 15t+24=24t-60 | | 4x=18-9 | | 3x+10-5x=6x-50 | | 2x^4=28x^2-90 | | A(n)=-3+(n-1)(-2.2) | | rd=q | | 86=n+33 | | -2t+75=29 | | 2x^4-28x^2-90=0 | | -3(6p+4)= | | 9+3x+4x=58 | | 2/7x-6=9/7x | | 3y-7=24 | | 2x-6x+3x-6+4x= | | 2X^2-32X-128=0 | | 32.50/5 | | 1x+4/3=10/6 |